1970
DOI: 10.3329/jdmc.v17i2.6595
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug Resistant Typhoid Fever in Children: A Review

Abstract: DOI: 10.3329/jdmc.v17i2.6595J Dhaka Med Coll. 2008; 17(2) : 121-126

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…These findings were in agreement with our previous study (17). Some authors also reported the growing resistance trend of ciprofloxacin against the pathogens causing enteric fever (18,19). These results are in agreement with previous studies (20,21).…”
Section: Resultssupporting
confidence: 89%
“…These findings were in agreement with our previous study (17). Some authors also reported the growing resistance trend of ciprofloxacin against the pathogens causing enteric fever (18,19). These results are in agreement with previous studies (20,21).…”
Section: Resultssupporting
confidence: 89%
“… 33 No azithromycin-resistant Salmonella and Shigella isolates were noted in our study, but have been reported in other places such as Bangladesh. 34 , 35 The emergence of antimicrobial resistance and multidrug-resistant bacteria are of the greatest global concern for the treatment of infections. Third-generation cephalosporins are being used increasingly for the treatment of diarrheal disease, 30 which can lead to increased prevalence of extended-spectrum beta lactamase bacteria, creating challenges in the treatment of more serious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Typhoid disease is endemic in many countries and the emergence of the multi-drug resistance (MDR) typhoid has become a huge global health threat [6]. Furthermore, in the last 20 years, multi-drug resistant (MDR) S. typhi strains have developed and spread worldwide, resulting in high rates of illness and death [8].…”
Section: Introductionmentioning
confidence: 99%